Flower Garden as a Short-Term Greening Effort for Embung Area in Srimulyo Village, Gondang District, Sragen Regency, Central Java - Nur Fauzi, Faiz; Siswanto, Budi (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2023)
A flower garden was created to green the embung area considering the dry season in August. The master plan used as a reference is a master plan made by the previous KKN period. In the execution process, the making of the flower garden has yet to be realized. Therefore, in this period of KKN, a flower garden was made west of the village pond. The flower garden created has a size of 8 x 2 meters with a distance of 30 cm between plants. There are 89 plants in this flower garden, namely 50 red purslane plants, 30 sabrina plants, and nine panca air plants. Making the garden begins with clearing the land and cleaning up the existing weeds. Then, the land measurement is carried out according to the desired garden size. After that, the process of tillage so that the soil can be planted with flower plants that have been prepared. The process of tillage is a process that takes much time. More than three days of new soil can be planted with flower plants. The obstacle faced in making this garden is the dry soil conditions, resulting in soil management that must be done with a long process.